Keravnou-Papailiou, Elpida - (:unkn) unknown (My University, 2026)
The main branch of Dr Keravnou-Papailiou’s research falls in the area of Artificial Intelligence in Medicine. She has been a member of the Editorial Board and subsequently Associate Editor of the scientific journal Artificial Intelligence in Medicine (Elsevier) that represents the premier forum for the publication of research results in this area, since its establishment in 1989.